Top executive compensation in Portuguese family firms - Pereira, I. N.; Esperança, J. P. (Corporate Ownership And Control, 2008)
Performance based compensation is considered a decisive tool in the co-alignment of interest between owners and managers. The solution to agency problems in public corporations hinges critically on the use of variable compensation mechanisms. Empirical analysis of this phenomenon is exiguous and the background theory has been suffering developments, like the introduction of family firm agency problems. This study confirms the larger use of variable compensation by public firms but shows that the potential for using variable compensation in second or third generation family firms is particularly high due to higher potential form conflict emergence between the different stakeholders. The framework used in this paper has the potential to encompass a wide range of phenomena where conflict can emerge and incentives can be used to co-align interests between the different transacting parties.